A high-performance solid-state lithium-oxygen battery with a ceramic-carbon nanostructured electrode. (August 2016) - Zhu, Xingbao; Zhao, Tianshou; Tan, Peng; Wei, Zhaohuan; Wu, Maochun
Abstract: Ceramic lithium-oxygen batteries that use non-flammable and non-volatile electrolyte have the potential to store a large amount of energy in a relatively safe way. However, the performance of this type of battery has been extremely low due primarily to the large ohmic-resistance from a thick electrolyte and the limited triple-phase boundaries (TPBs) in conventional cathodes. In this work, we fabricate a seamless electrolyte-electrode structure by one-step sintering a rather thin Li1.3 Al0.3 Ti1.7 (PO4 )3 (LATP) electrolyte layer (20 µm thick) onto a porous LATP substrate. A hierarchical carbon is then grown in the pores of the porous LATP, uniquely forming three-dimensional pathways for the transport of lithium-ions, electrons, and oxygen throughout the entire cathode. It is found that the cathodic TPBs are 330 times larger than those of conventional solid-state lithium-oxygen batteries. As a result, the battery is capable of operating in O2 for over 1174 cycles (~150 days) and for over 450 cycles (75 days) with degradation of <3% in ambient air when RuO2 and NiO are used as the catalysts. Moreover, the charge/discharge rate reaches as high as 15 mA cm −2, 2–4 orders of magnitude higher than that of conventional lithium-oxygen batteries. Graphical abstract: This work reports a significant progress in the fabrication of solid-state lithium-oxygen (air) batteries with a record performance by integrating a unique seamless electrolyte-electrode structure including a thin dense LATP electrolyte and a porous LATP, which can host carbon particles, carbon nanofibers and catalysts as cathode. Highlights: We fabricate a seamless electrolyte-electrode structure. The electrolyte layer is as thin as 20 µm as compared with conventional 300 µm. The triple-phase boundary increases by more than 300 times. The battery can operate in O2 for >1000 cycles and in air for >450 cycles. The discharge/charge rate increases by 100–1000 times.